Sarcoidosis and colon cancer: a possible association - Stanziola, Anna Agnese; Caccavo, Giovanna; De Rosa, Nicolina; D'Amato, Maria; Saggar, Rajeev; Spadaro, Giuseppe; Ponticiello, Antonio (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Sarcoidosis is a multisystem inflammatory disease characterized by non-caseating granulomas which mainly affect the pulmonary lymphatic system and lungs; although any organs can be interested. The association between sarcoidosis and cancer is still controversial, but many studies demonstrated an increased risk of cancer in patients with sarcoidosis, whereas few cases of sarcoidosis occurring after cancer have been reported. This report outlines and describes clinical, biologic and radiologic features of 3 patients with a history of surgical treatment and adjuvant chemotherapy for colon cancer, followed by a diagnosis of sarcoidosis some years later. The history of cancer and the lymph nodes positivity found through PET scan induced us to hypothesize a relapsing cancer disease. However, this hypothesis was not confirmed by the lymph nodes biopsy, which is the core method of diagnosis of sarcoidosis.